Delayed high-frequency suppression after automated single-pulse electrical stimulation identifies the seizure onset zone in patients with refractory epilepsy. Issue 11 (November 2018) - Davis, Tyler S.; Rolston, John D.; Bollo, Robert J.; House, Paul A.
Highlights: Automated single-pulse electrical stimulation evokes delayed high-frequency suppression (DHFS) in patients with refractory epilepsy. DHFS serves as a reliable marker of the seizure onset zone (SOZ). DHFS analysis may increase the speed and reproducibility of SOZ identification. Abstract: Objective: Single-pulse electrical stimulation (SPES) of intracranial electrodes evokes responses that may help identify the seizure onset zone (SOZ); however, lack of automation and response variability has limited clinical adoption of this technique. We evaluated whether automated delivery of low-current SPES could evoke delayed high-frequency suppression (DHFS) of ongoing electrocorticography (ECoG) signals that, when combined with objective analytic techniques, may provide a reliable marker of this zone. Methods: Low-current SPES (1-ms, 3.5-mA biphasic pulses) was delivered to 652 electrodes across 10 patients undergoing ECoG for seizure focus localization. DHFS was measured by calculating the normalized trial-averaged time-frequency power (70–250 Hz) 0.4–1 sec post-stimulation. Electrodes that evoked suppression when stimulated or recorded suppression when stimulation was nearby were used to estimate the SOZ. Results: The estimated SOZ significantly identified the clinical SOZ in 6 of 10 patients (5 of 7 temporal foci) with a false-positive rate of 0–0.06. Stimulation required <2 h, was undetectable by patients, and did not induce seizures or after-discharges. Conclusions: We show that DHFS provides accurate estimates of the clinical SOZ in patients with refractory epilepsy. Significance: This approach may increase the safety, speed, and reproducibility of SOZ identification while reducing cost, subjectivity, and patient discomfort.